2020
DOI: 10.1534/g3.119.400904
|View full text |Cite
|
Sign up to set email alerts
|

SNP-CRISPR: A Web Tool for SNP-Specific Genome Editing

Abstract: CRISPR-Cas9 is a powerful genome editing technology in which a single guide RNA (sgRNA) confers target site specificity to achieve Cas9-mediated genome editing. Numerous sgRNA design tools have been developed based on reference genomes for humans and model organisms. However, existing resources are not optimal as genetic mutations or single nucleotide polymorphisms (SNPs) within the targeting region affect the efficiency of CRISPR-based approaches by interfering with guide-target complementarity. To facilitate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Furthermore, both studies emphasize the need of common gRNA designs due to regulations and its consequential costs. Another recently published web tool, SNP-CRISPR, designs gRNAs for non-reference genomes to support allelic targeting (Chen et al, 2020). SNP-CRISPR calculates the gRNA efficiency score for the variant and the reference sequences.…”
Section: Snp-derived Pammentioning
confidence: 99%
“…Furthermore, both studies emphasize the need of common gRNA designs due to regulations and its consequential costs. Another recently published web tool, SNP-CRISPR, designs gRNAs for non-reference genomes to support allelic targeting (Chen et al, 2020). SNP-CRISPR calculates the gRNA efficiency score for the variant and the reference sequences.…”
Section: Snp-derived Pammentioning
confidence: 99%
“…Basically, SNP-CRISPR designs sgRNAs based on the public SNP database yet with only two types of PAM. 53 The other server, CrisPam, only analyzes the variants that produce novel PAMs (in PAM) from pathogenic and likely pathogenic SNPs in humans. 54 Interestingly, they found that 84% of the total SNPs checked can create novel PAMs, and the average number of PAMs generated by an SNP is 6.97.…”
Section: Comparison With Similar Serversmentioning
confidence: 99%
“…Another two web servers, SNP-CRISPR and CrisPam, were also recently developed, converging with our web tool, AsCRISPR, but at different publication status, to share the same notion of the allele-specific designing of sgRNAs. Basically, SNP-CRISPR designed the sgRNAs based on public SNP database yet with only two types of PAMs [41]. Another web server, CrisPam, only analyzed the variants that produce novel PAMs (In PAM) from pathogenic and likely-pathogenic SNPs in humans [42].…”
Section: Comparison With Similar Serversmentioning
confidence: 99%